Predicting cattle performance from mathematical models - B.E. Brent; A. Chestnut; P. George (Kansas Agricultural Experiment Station Research Reports, 1978)
Tables based on a mathematical model are presented that allow cost of gains by steers at various weights to be calculated. An example illustrate how to use the tables to help with economic decisions.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Performance; Gain